Effects of strength and plyometric training on vertical jump, linear sprint, and change-of-direction speed in female adolescent team sport athletes: A systematic review and meta-analysis - Luo, H.; Zhu, X.; Nasharuddin, N. A.; Kamalden, T. F. T.; Xiang, C. (Journal of Sports Science & Medicine, 2025)
This systematic review and meta-analysis examines the effects of strength training (ST) and plyometric training (PT) on vertical jump (VJ), linear sprint (LS), and change-of-direction speed (CODS) in female adolescent team sport athletes. Additionally, it explores potential moderator variables, such as programming variables and participant characteristics, that may influence these training effects. Eligibility criteria: Randomized controlled trials examining the effects of ST or PT interventions lasting =4 weeks on VJ, LS, or CODS in female adolescent team sport athletes (aged 10-19 years) were included. A systematic search was conducted in PubMed, Web of Science, Cochrane, Embase, and SPORTDiscus from inception to August 28, 2024. The risk of bias of the included studies was assessed using the latest version of the Cochrane risk-of-bias tool for randomized trials (ROB-2). Meta-analyses were performed in Stata15.0 using random-effects models. Subgroup analyses were conducted based on the participant characteristics (age, height, weight, and type of sports) and programming variables (duration, frequency, and total sessions). Twenty-six studies involving 705 female adolescent team sport athletes were included. Meta-analyses revealed that ST and PT exhibited significant (p < 0.05) and moderate to large effects on VJ (ST, ES: 0.74, moderate; PT, ES: 0.87, moderate), LS (ST, ES: -1.26, large; PT, ES: -1.23, large), and CODS (ST, ES: -1.16, moderate; PT, ES: -1.20, moderate). Subgroup analysis indicated that for ST, training protocols of = 10 weeks, = 2 sessions/week, or = 20 sessions were more effective. ST also showed greater benefits for athletes > 15 years old (LS), = 163 cm (LS, CODS), = 63 kg, and handball players. For PT, protocols of > 9 weeks, > 14 sessions (VJ), or = 18 sessions (CODS) were more effective, with handball players responding best to PT. The overall risk of bias of the included studies was judged as moderate. The certainty of evidence was rated as moderate to high based on the GRADE approach. Both ST and PT are effective in improving VJ, LS, and CODS in female adolescent team sport athletes. Longer duration, lower frequency, or fewer sessions of ST produce better effects. Older and more mature athletes are better adapted to ST, likely due to increased muscle mass, hormonal factors, and neuromuscular adaptations. Longer duration or more sessions of PT produce better effects. Handball players showed a greater response to both ST and PT than athletes of other sports, according to observed trends.